Static control-flow analysis for reverse engineering of UML sequence diagrams. - Rountev, Atanas (Software engineering notes.)
UML sequence diagrams are commonly used to represent the interactions among collaborating objects. Reverse-engineered sequence diagrams are constructed from existing code, and have a variety of uses in software development, maintenance, and testing. In static analysis for such reverse engineering, an open question is how to represent the intraprocedural flow of control from the code using the control-flow primitives of UML 2.0. We propose simple UML extensions that are necessary to capture general flow of control. The paper describes an algorithm for mapping a reducible exception-free intraprocedural control-flow graph to UML, using the proposed extensions. We also investigate the inherent tradeoffs of different problem solutions, and discuss their implications for reverse-engineering tools. This work is a substantial step towards providing high-quality tool support for effective and efficient reverse engineering of UML sequence diagrams.